Leadership styles, organizational learning and organizational competitiveness: evidence from the Republic of North Macedonia - Krsteska, Kristina; Arikan, Cenk Lacin; Mitrevski, Viktor; Smilevski, Cvetko (Serbian Journal of Management, 2023)
This study, in the Republic of North Macedonia (NM), identifies the differences between the Leadership Styles (LS) in the given context of Organizational Learning (OL), Situational Leadership (SL), and Organizational Competitiveness (OC). In addition, the study identifies specific factors which make up these constructs. The research was conducted across several industries, organizational hierarchical levels, and various work experiences. A pre-test survey was conducted on a small scale of respondents (n=79) for Organizational learning questionnaire, while the final questionnaire was administered on a larger scale (n=273), both using the convenient sampling. Results prove that there are no statistically significant differences between LS in OC, nor in the OL, while statistically significant differences existed in SL. This study also explored the existing multiple factors in LS, OL, and OC. These findings shed light on possible future research which can integrate these results and dive into further exploratory studies that can dwell into more comprehensive understanding which in effect can increase managerial implications for companies and researchers alike.
Keywords: leadership styles; organizational learning; organizational competitiveness